KARAKTERISTIK PETERNAK TERHADAP KEMAMPUAN BETERNAK SAPI POTONG DI KELURAHAN KLAMPOK KECAMATAN SANANWETAN KOTA BLITAR - Achmad Sambodo; Agustina Widyasworo; Resti Yuliana Rahmawati (Universitas Islam Balitar, 2020)
This study aims to determine the characteristics of breeders with regard to the ability to keep beef cattle in Klampok Village, Sananwetan District, Blitar City. The material in this study concerns beef cattle farms in Klampok sub-district, sananwetan sub-district, Blitar city using quantitative research methods in the form of case studies with 33 farmer respondents. Data collection methods are conducted through surveys, pre-questioned interviews and observation. The results obtained from this study are that the ability to raise beef cattle is appropriate in the category. Breeding experience has a significant effect on the ability to keep beef cattle, as Klampok has had a business for raising beef cattle for a long time, while age and education level have no effect because age and education level in the study area are relative. uniform so that they have no effect, then the number of animal possession has no effect. because the breeders in the Klampok sub-district consider beef cattle only as an afterthought, so it has no significant effect on the ability to keep beef cattle